PSYCHOSOCIAL RISK ASSESSMENT AND MANAGEMENT: CRITICAL APPRAISAL AND ADVANCEMENT OF MALAYSIA's PRiSMA 2024 GUIDELINES - Abd Shukor, Sutiman; Khalid, Mohd Shamsuri (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The critical appraisal and advancement of Malaysia’s PRiSMA 2024 Guidelines signify a pivotal step in the nation’s commitment to the management of psychosocial hazards as part of Occupational Health and Safety (OHS) frameworks. This paper evaluates the shifting landscape of modern workplaces, emphasizing how psychosocial risks have emerged as fundamental factors influencing employee well-being and organizational success, underscored by mounting evidence from international agencies and adverse workplace outcomes. The enactment of the Occupational Safety and Health Amendment Act 2022 renders psychosocial risk management a statutory requirement, placing Malaysia at the forefront of legislative progress in Asia and harmonizing its practice with global standards such as ISO 45003. A central contribution of this work is its detailed exposition of the PRiSMA framework’s operational logic, toolset, and process flow. The PRiSMA guidelines incorporate a proactive and preventative approach, utilizing tools such as the Likelihood of Environmental Occupational Exposure (LEO26) scale, the Employer Practice Checklist (EPC23), and the PRiSMA intervention matrix to link risk screening, control assessment, and evidence-based action. The theoretical foundation is deeply rooted in the Job Demand-Control-Support (JDCS) model and further incorporates elements from the more recent Job Demands-Resources (JD-R) and Psychosocial Safety Climate (PSC) frameworks. It proposes a dual-layered system that addresses both job-specific risks and organizational climate. Critical analysis highlights gaps in the psychometric validation of PRiSMA’s assessment tools, suggesting that future research should prioritize rigorous instrument evaluation, large-scale field studies, and transparent publication of reliability and validity data. The paper further notes practical implementation challenges, citing organizational inertia, siloed management, and the need for interdisciplinary leadership and participatory approaches, and recommends linking psychosocial safety initiatives to ESG strategies for sustainable organizational change. By conjoining legal imperatives, practical guidelines, and rich theoretical perspectives, this research solidifies PRiSMA as a mandatory national standard. It offers a pathway for scientific and organizational advancement toward fostering mentally healthier, more resilient, and productive Malaysian workplaces.